(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Nature has been a source of medicinal agents for thousands of years and an impressive number of medicinal drugs have been isolated from natural resources. It is now a known fact that nature has given cure of every disease in one way or another but the only need is to explore them wisely. So the researchers today are emphasizing on evolution & characterization of various plants & plant constituents against different diseases. The essential uses of many plants have been worked out & published but many useful and valuable plants are still unexplored upto date. One such plant/drug is Tridax procumbens Linn commonly called as coat button in English and Ghamra in Hindi. Though it has been used in folklore practices for hundreds of years but still it is considered a useless weed in many parts of the world. It is a multifaceted weed available throughout the continent which can act as a substitute for many herbs. The present endeavour is an attempt to analyse the updated information of Tridax identification, phytochemical, pharmacogonostic study and its pharmacological activities like hepatoprotective activity, antimicrobial activity, immunomodulating property, defluoridation activity, hypotensive action, anti viral action, anti oxidant action, antiurolithiatic action and anti inflammatory action to serve the ailing mankind by its magical action.